“Hearken to the Hermit-Thrush”1: A Case Study in Interdisciplinary Listening - Doolittle, Emily L. (Frontiers in Psychology, 2020)
Birdsong is widely analysed and discussed by people coming from both musical and scientific backgrounds. Both approaches provide valuable insight, but I argue that it is only through combining musical and scientific points of view, as well as perspectives from more tangentially related fields, that we can obtain the best possible understanding of birdsong. In this paper I discuss how my own training as a musician, and in particular as a composer, affects how I listen to and parse birdsong. I identify nine areas of overlap between human music and birdsong, which may serve as starting points both for musical and scientific analysis, as well as for interdisciplinary analysis as practiced in the developing field of “zoomusicology”. Using the hermit thrush (Catharus guttatus) as an example, I discuss how the song of a single species has been described by writers from a variety of disciplines, including music, literature, and the sciences, as well as how we can contextualise these varied perspectives in terms of broader cultural thought trends. I end with discussion of how combining approaches from multiple fields can help us to figure out new questions to ask, can help us identify how our own cultural biases may affect how we hear birdsong, and ultimately can help us develop richer and more nuanced understandings of the songs themselves.